Model of Strategic Disinformation Reconstruction Based on Analysis of Intentions - Yuskiv, Bohdan; Karpchuk, Nataliia; Fedoniuk, Serhii (Politologija, 2024)
Disinformation is a powerful means of manipulation in times of conflicts and war and fake news is a disinformation tool. The Russian Federation disseminates disinformation to support its military and foreign political goals. This article offers a theoretical contribution to exploring the role of intentions in disinformation strategies. In this research, we developed a FIRS model for detecting hidden disinformation strategies in fake news and attempted to identify the Russian disinformation strategy regarding Ukraine during the first year of the RF’s full-scale invasion of Ukraine. The article addresses the question of whether it is possible to comprehend the overall strategy of disinformation influence by reconstructing the intentions of fake news. Relying on intent analysis, intentions correlations analysis and intentions clustering method, the article highlights the RF’s manipulative intentions, namely, discrediting Ukraine, discrediting the West, justification of the RF’s actions, the RF’s positive image and criticism of opponents, demonstration of the RF’s power and intimidation of the opponents, accusing Ukraine and the West of nazism. The results demonstrate the systemic nature of the RF’s disinformation strategies and their adaptation to the course of the war.
Keywords: disinformation,; fake news; intention; clusterisation; correlations analysis; Ukraine; Russian Federation